ANALISIS PENGARUH STOCK SELECTION SKILL, MARKET TIMING ABILITY, FUND LONGEVITY, FUND CASH FLOW DAN FUND SIZE TERHADAP KINERJA REKSADANA (Studi Kasus: Reksadana Saham Periode 2010-2014) - Syahid, Nur; Arfianto, Erman Denny (Diponegoro Journal of Management, 2015)
Investment growth of mutual funds in Indonesia has increased rapidly due to the mutual fund that able to overcome the investor problems in making investment. The problems associated with time, information, and the ability to invest. Mutual funds are managed by an investment manager that can manage the fund in accordance with its investment objectives.This study conducted to examine the relationship between the performance of mutual fund shares with five variables that affect it includes stock selection skills, market timing ability, longevity fund, fund cash flow and fund size. The data used in this study are SBI, JCI, TNA annually, NAB monthly, and age with 59 sample of mutual funds of stocks for 2010-2014 period and the number of observations as many as 188 data.This research using the method of multiple linear regression with the classical assumption using normality test, heteroscedasticity test, multicollinearity test, autocorrelation test. The method used to test the hypothesis is the F test and T test shows that partially market timing ability have significant positive impact to performance of mutual funds. Stock selection skill have significant negative impact to performance, but Fund Longevity and Fund Size have no significant negative impact to performance of mutual funds. Then cash have no significant positive impact to performance of mutual funds. Based on the test results show the value of the coefficient of determination adjusted R square of 0.633, so that the variables in this study may explain the variable performance of mutual funds amounted to 63.3%.